Warm Power in the Digital Age: Niche Communication and Thai-Localized Narratives in Guangxi’s Cross-Border Social Media Practices - Yuan Xu (Sinolingua: Journal of Chinese Studies, 2026)
This study examines how local mainstream media in China construct “warm power” through localized international communication practices, taking Guangxi’s Thailand-oriented communication as the primary case, with Yunnan’s Myanmar-oriented practices as a comparative reference. Against the backdrop of deepening China–ASEAN relations and the limitations of traditional soft power in the social media era, the study adopts a qualitative case-based design integrating document analysis, qualitative content analysis, and comparative interpretation. The findings reveal that Guangxi’s international communication has evolved from fragmented media operations toward a coordinated warm power ecosystem characterized by strategic hub coordination, platform-based audience segmentation, culturally localized narratives, and sustained affective interaction. Through Thai-localized storytelling, people-centered everyday narratives, and integrated online–offline engagement, Guangxi’s media practices have shifted the logic of influence from symbolic image display to relationship-oriented communication, fostering emotional resonance, trust, and early forms of cross-cultural affective communities. Comparative observations from Yunnan further demonstrate that cultural proximity, audience segmentation, and “warm interaction” are key enabling conditions for warm power diffusion in Southeast Asia. Theoretically, this study advances the concept of warm power as a form of relational influence grounded in affective connectivity and sustained interaction, enriching international communication theory with a regionally embedded perspective. Practically, it highlights the unique role of local media as affective interfaces in China’s international communication system and offers insights for enhancing people-to-people connectivity and cross-cultural understanding in the ASEAN context.